Novel homozygous variants in TTC12 cause male infertility with asthenoteratozoospermia owing to dynein arm complex and mitochondrial sheath defects in flagella - Meng, Lanlan; Liu, Qiang; Tan, Chen; Xu, Xilin; He, Wenbin; Hu, Tongyao; Tu, Chaofeng; Li, Yong; Du, Juan; Zhang, Qianjun; Lu, Guangxiu; Fan, Li-Qing; et al. (Frontiers in Cell and Developmental Biology, 2023)
Introduction: Tracing the genetic causes for male infertility due to asthenoteratozoospermia has revealed at least 40 causative genes, which provides valuable reference for the genetic testing of asthenoteratozoospermia in clinical practice. To identify deleterious variants in the human tetratricopeptide repeat domain 12 (TTC12) gene in a large cohort of infertile Chinese males with asthenoteratozoospermia. Methods: A total of 314 unrelated asthenoteratozoospermia-affected men were recruited for whole exome sequencing. The effects of the identified variants were evaluated by in silico analysis, and confirmed by in vitro experiments. Intracytoplasmic sperm injection (ICSI) was used to evaluate the efficiency of assisted reproduction technique therapy. Results and Discussion: Novel homozygous TTC12 variants (c.1467_1467delG (p.Asp490Thrfs*14), c.1139_1139delA (p.His380Profs*4), and c.1117G>A (p.Gly373Arg)) were identified in three (0.96%) of the 314 cases. Three mutants were indicated to be damaging using in silico prediction tools, and were further confirmed by in vitro functional analysis. Hematoxylin and eosin staining and ultrastructural observation of the spermatozoa revealed multiple morphological abnormalities of flagella, with the absence of outer and inner dynein arms. Notably, significant mitochondrial sheath malformations were also observed in the sperm flagella. Immunostaining assays indicated that TTC12 is present throughout the flagella, and was strongly concentrated in the mid-piece in control spermatozoa. However, spermatozoa from TTC12-mutated individuals exhibited almost no staining intensity of TTC12 and outer and inner dynein arms components. The three men accepted ICSI treatment using their ejaculated spermatozoa, and two female partners successfully delivered healthy babies. Our findings provide direct genetic evidence that homozygous variants in TTC12 cause male infertility with asthenoteratozoospermia by causing dynein arm complex defects and mitochondrial sheath malformations in the flagellar. We also demonstrated that TTC12 deficiency-mediated infertility could be overcome by ICSI technology.